Estimates of the Kolmogorov widths for classes of infinitely differentiable periodic functions - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Lower estimates of the Kolmogorov widths are obtained for certain classes of infinitely differentiable periodic functions in the metrics of C and L. For many important cases, these estimates coincide with the values of the best approximations of convolution classes by trigonometric polynomials calculated by Nagy, and, hence, they are exact.